Pengaruh Redesain Kebijakan Kelas Rawat Inap Standar (KRIS) terhadap Kualitas Pelayanan Medis Pasien JKN di Rumah Sakit Umum Daerah - Syahriani Lamusi; Sri Putri Gusasi; Adelina Anggriani Usman; Zulvikar Kasim (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The Standard Inpatient Class policy (Kelas Rawat Inap Standar/KRIS) is a major step toward transforming Indonesia's National Health Insurance (JKN) system. The core goal is to remove the gap in service quality that was once tied to membership class. Under the old system, patients were placed in wards based on how much premium they paid. KRIS replaces that structure with a single minimum standard covering 12 criteria that focus on patient safety and infection prevention. This study aims to examine how the KRIS policy redesign affects the quality of medical services received by JKN patients at Regional General Hospitals (RSUD), covering aspects such as facility readiness, human resources, financing mechanisms, patient satisfaction, and barriers to implementation. This study uses a simple qualitative approach through document analysis and field observation at RSUD. Data were collected through in-depth interviews with hospital staff and JKN patients, supplemented by observation of ward conditions and review of relevant policy documents. The findings show that infrastructure gaps remain a significant problem. Only 15.87% of beds at RSUD Kota Bandung met all 12 KRIS criteria as of July 2024, while private pilot hospitals reached 100%. Limited budgets, shortage of trained staff, and lack of physical space are the main barriers. Digital services through the Mobile JKN application show a strong link with patient satisfaction, particularly in the efficiency dimension (r=0.748). Performance-based capitation at primary health facilities also has a positive but variable effect depending on available resources. The study concludes that achieving equitable medical service quality under KRIS requires coordinated support from regional budgets, policy harmonization, workforce development, and broad public communication.